Peningkatan Kecekapan Pengurusan Agensi melalui Pendekatan Pendigitalan Dokumen (Sains Humanika, 2018)
Digitization of documents ensures efficient, quick, and cost saving of official documentation. It would realize the concept of digital campus and green technology. It also in line with the ISO 15489 — Information and Documentation—Records Management 2001. The digitization of the university documents is made centralized at the Center for Knowledge and Communication Services. The undertaking was approved by the university’s administration in 2016. The idea was that the office monitors the work flows of the document digitization from the initiation phase to completion phase. The study that took place in 2016 had made the office the first department where the study was carried out. Later, it will be implemented by the other departments. The digitization processes were developed by data management unit and the implementation was accomplished by the Knowledge and Communication Services Centre. The whole operation is performed by seven personnel that consists of one assistant information technology officer and six assistant operational officers. This work identifies the factors that affect the performance of document management. It tackles the perception of university employees who are engaged in administrative and management of documentation. The idea is to enhance the management performance on the digitization of the organization records. A total of 80 respondents from the faculty and the non-academic units or centers were selected to participate in the survey. The questionnaire has a 0.944 level of the reliability (Cronbach's α). It is greater than 0.7 that indicates the survey instrument is reliable. The data was processed through exploratory factor analysis to see the structure of the organization’s performance factors. The results pinpoint the key elements that would affect the performance of document management. It is concluded that the important elements in increasing the efficiency of managing documentations in the university may be identified.
Keywords: Documentation; policy and guidelines; employee performance; information technology and communication